2020
DOI: 10.1021/acs.chemrev.0c00394
|View full text |Cite
|
Sign up to set email alerts
|

Microkinetic Modeling: A Tool for Rational Catalyst Design

Abstract: The design of heterogeneous catalysts relies on understanding the fundamental surface kinetics that controls catalyst performance, and microkinetic modeling is a tool that can help the researcher in streamlining the process of catalyst design. Microkinetic modeling is used to identify critical reaction intermediates and rate-determining elementary reactions, thereby providing vital information for designing an improved catalyst. In this review, we summarize general procedures for developing microkinetic models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
204
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(235 citation statements)
references
References 294 publications
0
204
0
Order By: Relevance
“…Consistency of reaction steps across the different sites would lead to an explosion in the number of parameters to be fitted and cross-correlation between the parameters. Thus, according to the microkinetic method proposed by Dumesic et al 77,78 , the desire to include all reaction intermediates on the catalyst surface is balanced with the need to express the mechanism in terms of kinetic parameters that are accessible to experimental measurements or theoretical prediction. This compromise between the mechanistic detail and kinetic parameter estimation plays an important role in the use of microkinetic analysis for catalytic reaction synthesis.…”
Section: Comparison Between Tpd and Tpsr Profilesmentioning
confidence: 99%
“…Consistency of reaction steps across the different sites would lead to an explosion in the number of parameters to be fitted and cross-correlation between the parameters. Thus, according to the microkinetic method proposed by Dumesic et al 77,78 , the desire to include all reaction intermediates on the catalyst surface is balanced with the need to express the mechanism in terms of kinetic parameters that are accessible to experimental measurements or theoretical prediction. This compromise between the mechanistic detail and kinetic parameter estimation plays an important role in the use of microkinetic analysis for catalytic reaction synthesis.…”
Section: Comparison Between Tpd and Tpsr Profilesmentioning
confidence: 99%
“…Next, the information about the reaction rates is used to formulate coupled differential equations for each elementary step which are then solved numerically for a given set of initial conditions, with further details reviewed recently by Motagamwala and Dumesic. 164 In this way, MKM connects quantitatively molecular-level modeling with experimental data by using as inputs the outputs obtained from first-principles calculations. MKM is particularly relevant in heterogeneous catalysis because it provides a description of complex reactions by identifying key reaction intermediates and the rate-limiting step, which ultimately controls the catalytic performance.…”
Section: Microkinetic Modelingmentioning
confidence: 99%
“…Reaction kinetic data are used extensively in reactor design [1,2]. While even simple power law expressions can sometimes be used in simulation of industrial reactors [3], such an approach has a limited insight into the reaction mechanism and can be applied only in a limited range of reaction conditions [4]. More complex reaction mechanisms, such as those usually referred to as Langmuir-Hinshelwood or Eley-Rideal [1] mechanisms assume quasi-equilibria of adsorption/desorption steps and certain rate determining steps.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] it was suggested that theoretically sound values of pre-exponential factors, activation energies, adsorption enthalpy and entropy, distribution functions for the number of actives sites with different heats of adsorption, Polanyi parameters for elementary steps, etc., should be introduced as an input to computer subroutines. A more refined methodology coined microkinetic modelling [4,[13][14][15][16], has become a widespread approach to incorporate the essential features of surface chemistry. For relatively simple cases, such as ammonia synthesis, based on the surface science data it is possible to describe the experimental observations without any fitting of the parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation